Identification of AHR and hypoxia co-regulated immune target genes as potential factors of inflammation-driven oncogenesis - Zaiden, Norazean (2015)
The transcription factors AHR and HIFs dimerize with the common co-activator ARNT during adaptive responses to xenobiotic exposure and oxygen tension. This cross-talk may subsequently modulate inflammation and/or physiological adaptation via immune cellular survival and maturation. Dysregulation of AHR and HIF pathways can cause chronic inflammation leading to oncogenesis, thus we hypothesized that AHR and hypoxia signaling co-operate in potentiating inflammation-driven oncogenesis. To address this, we analyzed AHR-mediated transcriptional responses in three frequently xenobiotic-exposed study models (murine liver, human keratinocytes, human intestinal epithelial cells), especially in the intestine, where AHR and hypoxia signaling constantly co-exist. Although AHR signaling is evolutionary conserved, we find that the AHR mediates diverse responses in a cell type- and species-dependent manner. Concurrent activation with hypoxia signaling in intestinal cells indicate a promotion of chronic inflammation through down-regulation of numerous anti-inflammatory target genes, and up-regulation of pro-inflammatory genes such as PTGS2, GZMB, and MMP1.